Troubleshooting Techniques of Complex Multi-Layered PCBs - Mirza Salman Baig; Ambreen Insaf (Journal of Basic & Applied Sciences, 2021)
In this modern era where technology is rapidly changing and is being advanced day by day, Pakistan is dependent on foreign OEM (Original Equipment Manufacturer) for the functional supportability of the systems because most of the commercial and non-commercial systems are foreign OEM based. In the case of any defect of the systems and to reduce the dependency on OEM, the simplest way is to troubleshoot the PCBs (Printed Circuit boards) of the system locally instead of purchasing new PCB or sending it back to OEM for repair until we are able to design our own systems. Thus, it won’t be wrong saying “time, tide and technology wait for none”. The purpose of this research is to achieve self-reliance in PCB troubleshooting, thereby reducing dependability on foreign OEMs, equipment downtime and high costs being acquired in PCB repairs, secondly to highlight the importance of this field so that universities may adopt it as a subject. This research paper is based on some troubleshooting techniques for repair of complex multilayered PCBs.